Menggali Kemampuan Guru Bidang IT dalam Melakukan Kegiatan Belajar Mengajar - Hery Noer Aly; Bustomi Hasan; Mawardi Lubis (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study explores teachers' technological approaches to learning activities during a pandemic disruption. The teachers' role in solving learning activity problems during education disruption was essential. So, the expected learning outcomes can be achieved as optimally as possible. We have searched for data on book application sources and other scientific works that can be used to answer research problems. As for the review, we have analyzed the data involving data coding, interpretation, evaluating, and making conclusions to find these findings relevant to validity and reliability. After conducting an in-depth study and discussion, we finally have informed several points, including the technology approach; teachers are dominant and play a key role in implementing learning during the policy of closing schools but opening small classes remotely. We hope this finding is helpful for the following study in a relevant context.